ENGLISH LANGUAGE ANXIETY AMONG MALAYSIAN SIAMESE STUDENTS: EXPLORING THE CONTRIBUTING FACTORS - Noormaizatul Akmar Muhamad Nasir; Nurul Husna Yaacob; Radzuwan Ab Rashid (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study examined the English language anxiety of Siamese students as one of the minority ethnicities in Malaysia. The consequences of untreated anxiety and depression among students cannot be underestimated, as they are vulnerable to various social and behavioral problems, compromised learning performance, and diminished self-esteem. To delve into this issue, a total of 113 Malaysian Siamese students attending national and national type-secondary schools with a minimum of seven years of experience learning English filled up the Foreign Language Anxiety Scale (FLCAS), a popularly used instrument to measure foreign language anxiety among learners. The findings revealed items categorised under the fear of negative evaluation as the most likely to provoke anxiety among the students, whereas components covering anxieties in English tests reported the lowest. The results generally indicate that minority Siamese students view evaluation by others as more anxious than being academically tested. Hence, teachers are recommended to be more particular in planning and designing English lessons in multiracial classrooms so the anxiety-provoking vibes can be handled appropriately.